Generation Alpha Numeracy Learning Assistance with Anti-Gadget Media at SDN Tongas Wetan IV Probolinggo - Rizal, Hasan Syaiful; Triwahyuni, Dicha Riski; Akmaliah, Vika Zida; Kamara, Yusufu (LPPM Universitas Yudharta Pasuruan, 2023)
The numeracy skills of SDN Tongas Wetan IV students are at a low level. The school is located in the remote Tongas Wetan village, surrounded by rice fields, with limited road access. Unfortunately, the absence of a cable or Wi-Fi internet network hinders technological adaptation and forces the numeracy learning process in the classroom to rely primarily on classical methods, with minimal use of learning media. Therefore, it is essential to assist students in learning numeracy using media that do not require the use of gadgets. To address this issue, a service-learning approach is employed to assist SDN Tongas Wetan IV students in three stages: the preparation stage, mentoring stage, and reflection stage. This assistance aims to create various simple learning media that can be utilized in the numeracy learning process without the need for gadgets. As a result, students become more enthusiastic and active participants in the learning process of numeracy. The positive response from the teacher indicates that the learning interactions have become more interesting. Additionally, students' numeracy skills have demonstrated an average increase of 30.47%.